Vitual diaspora: process of idetification and belonging in a virtual learning community (Research, Society and Development, 2020)
In this article we will seek to uderstand some of the cultural implications that are part of identity constitution of the subject, considering the context concepts, space and temporality on a Virtual Learning Community. The research envolve a reflective study, of qualitative approach that defined the critical ethnosearch as a theoretical-methodological way, having the epistemology of complexity for a creation of method in a strict posture of scientific bricolage. The investigation occurred starting from a extension course, offered in a program of postgraduate, for teachers that acted in different teaching levels. The results and analysis evidenced that the feeling of belonging, the territoriality, the permanence, the emotional connections, collaborative character, the sharing of a solidarity project, of  conflicting goals and the trust are some guiding principles of the convivence in CVA and are required for the establishing of links, once the actors need implicate themselves, develop the autonomy and promote mediations through subjective marks printed on the interfaces of a virtual learning envoriment, because only that way will constitute in authors-actors.